2019
DOI: 10.24057/2071-9388-2019-32
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Conditions Of Zakamensk Town (Dzhida River Basin Hotspot)

Abstract: Ecological problems of zakamensk town are associated with sand deposits that were formed as a result of mining activities of former Dzhidinsky tungstenmolybdenum plant. Sands are accumulated in large quantities and they contain dangerous concentrations of heavy metals. Desertification in an urbanized area is manifested locally, but it differs from agricultural desertification by a profound and comprehensive destructive change in the components of the environment. Maps of soils, vegetation, types of lands, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The Selenga River faces several socioeconomic and environmental impacts, influencing Lake Baikal ( Borisova, 2019 ). The anthropogenic impact on ecosystems in the Selenga River basin has increased in the recent decades, e.g., by the extraction of minerals, primarily gold, urbanization, and agricultural development, especially in the upper Mongolian part of the basin ( Jarsjö et al, 2017 ; Garmaev et al, 2019 ). The long-term low water period observed in the region ( Gelfan and Millionshchikova, 2018 ) has a significant impact on delta processes and wetland-dominated areas of the SRD, also posing drastic changes in sediment transport and water quality ( Chalov et al, 2017b ; Shinkareva et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…The Selenga River faces several socioeconomic and environmental impacts, influencing Lake Baikal ( Borisova, 2019 ). The anthropogenic impact on ecosystems in the Selenga River basin has increased in the recent decades, e.g., by the extraction of minerals, primarily gold, urbanization, and agricultural development, especially in the upper Mongolian part of the basin ( Jarsjö et al, 2017 ; Garmaev et al, 2019 ). The long-term low water period observed in the region ( Gelfan and Millionshchikova, 2018 ) has a significant impact on delta processes and wetland-dominated areas of the SRD, also posing drastic changes in sediment transport and water quality ( Chalov et al, 2017b ; Shinkareva et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Due to the lithochemical features of the lower Selenga basin, its waters are enriched with chemical elements (Fe, Zn, Mo, Cu), with concentrations corresponding to world-average values [10]. The main sources of river pollution are associated with the poorly treated industrial and municipal wastewaters from Ulan-Ude, Selenginsk, and Kabansk cities [11], as well as from cities of Mongolia [12]. The large inland delta (over 500 km 2 ) is considered as an important geochemical buffer to protect Lake Baikal [13,14].…”
Section: Methodsmentioning
confidence: 99%
“…Multi-scale modelling ranged from the basin-wide (Malsy et al, 2017;Frolova et al, 2017) to specific sub-regions, such as particular segments of the river system (Kaus et al, 2017;Thorslund et al, 2017;Garmaev et al, 2019) or its delta (S. R. Shinkareva et al, 2019), and identified reactions of hydrogeochemical pathways to climate change. The mean flow reduction in the Selenga River was 3 %-5 % during the 2020s to 2030s and 4 %-25 % during the 2080s to 2090s, being a crucial driver of ongoing and future hydrogeochemical changes.…”
Section: Lake Ice Covermentioning
confidence: 99%